2019
DOI: 10.7498/aps.68.20190245
|View full text |Cite
|
Sign up to set email alerts
|

Sound insulation performance of thin-film acoustic metamaterials based on piezoelectric materials

Abstract: Aiming at the isolation of low-frequency sound, a kind of thin-film acoustic metamaterialis designed and obtained by implanting PZT into thin film. The finite element method (FEM) of the structure is built, and 1<sup>st</sup>–14<sup>th</sup> order eigenfrequencies and transmission loss between 20–1200 Hz are calculated. The reliability of finite element calculation is verified experimentally and the existence of adjustable sound insulation peak is monitored in the experiment. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…When the content of ammonium polyphosphate is 20 PHR, the horizontal combustion rate can reach FH.1 level. e study also found that the higher the content of ammonium polyphosphate, the lower the compressive strength, the higher the thermal conductivity, and the higher the linear expansion coefficient of EPS material [7]. Lu used thermosetting phenolic resin and aluminum hydroxide mixed flame retardant liquid to flame retardant cover polystyrene particles to change the combustion essence of combustion droplets and shrinkage of polystyrene insulation board.…”
Section: Literature Reviewmentioning
confidence: 97%
“…When the content of ammonium polyphosphate is 20 PHR, the horizontal combustion rate can reach FH.1 level. e study also found that the higher the content of ammonium polyphosphate, the lower the compressive strength, the higher the thermal conductivity, and the higher the linear expansion coefficient of EPS material [7]. Lu used thermosetting phenolic resin and aluminum hydroxide mixed flame retardant liquid to flame retardant cover polystyrene particles to change the combustion essence of combustion droplets and shrinkage of polystyrene insulation board.…”
Section: Literature Reviewmentioning
confidence: 97%
“…(b)Novel thin film acoustic metamaterials for external circuits. Reproduced with permission from [36]. (c) The distributed structure thin-film acoustic metamaterial is composed of four metal foils and a cross-shaped flexible vinyl acetate (EVA) material swing arm.…”
Section: Resonant-type Amsmentioning
confidence: 99%
“…Mei et al [35] proposed a thin-film AM decorated with asymmetric rigid lamellae (see figure 2(a)) that can completely absorb low-frequency airborne sound at selective resonance frequencies in the range of 100-1000 Hz. In 2019, Zi-Hou et al [36] proposed a novel AM with piezoelectrics connected to external circuits embedded in a tensioned elastic membrane(see figure 2(b)). Zhou et al [37] presented a lowfrequency AMs with a frequency range of 20-1200 Hz (see figure 2(c)).…”
Section: Membrane-type Amsmentioning
confidence: 99%
“…Piezoelectric ceramic transducer element PZT-5 H used in the driver and sensor purchased from Shenzhen Furong Electroacoustic Technology Co., Ltd, the diameter size of 15 mm, resonant frequency of 10.5 kHz, as shown in figure 3. Table 1 shows the material parameters of PZT [23], where ρ is the density, S E 11 is the elastic compliance coefficient, d 31 is the piezoelectric strain constant, ε T 33 is the free dielectric constant in the direction perpendicular to the film surface, and ν is the Poisson's ratio.…”
Section: Selection Of Piezoelectric Ceramicsmentioning
confidence: 99%